Mapping the potentials of blockchain in improving supply chain performance - Luh Putu Mahyuni; Richard Adrian; Sri Darma; Ngakan Nyoman Kutha Krisnawijaya; I Agung Pradnya Dewi; Gusi Putu Lestara Permana (Cogent Business & Management, 2020)
This paper aims at reviewing and systematically mapping research on blockchain potentials in improving supply chain performance. Articles were retrieved from several prominent databases, selected, reviewed, grouped into several themes and synthesized. This paper suggests that applying blockchain in the supply chain could improve its performance in terms of transparency, traceability, sustainability, trust, and cost-efficiency. As a cutting-edge technology, blockchain has not been widely implemented in supply chain industries. Research on blockchain application in the supply chain is also relatively limited. This paper contributes to the literature by offering a comprehensive map of research on blockchain potentials in improving supply chain performance. The findings of this study will also be beneficial for managers who seek for a comprehensive understanding of how blockchain technology affects their companies particularly in supply chain management.
Keywords: 650; blockchain potentials; supply chain performance; transparency; traceability; sustainability; trust; cost-efficiency